AB0052 ROLE OF TRAINED IMMUNITY AND IMMUNOMETABOLISM IN THE PATHOGENESIS OF ERDHEIM-CHESTER DISEASE. (2nd June 2020) - Biavasco, R.; Molteni, R.; Stefanoni, D.; Ferrarini, M.; Ferrero, E.; Cenci, S.; Cardaci, S.; Boletta, A.; Cassina, L.; Di Stefano, G.; Dominguez Andres, J.; Doglioni, C.; et al.
Abstract : Background: Erdheim-Chester disease (ECD) is a chronic inflammatory disease characterized by infiltration of bone and other tissues by foamy macrophages. These cells exhibit activating mutations along the MAPK pathway, most commonly BRAFV600E, and increased production of pro-inflammatory cytokines. Although this dual neoplastic-inflammatory nature of ECD has long fascinated scientists, the mechanistic link between these two features remains elusive. We hypothesized that Trained Immunity (TI), a pro-inflammatory cell program physiologically elicited in monocytes/macrophages upon activation of the MAPK pathway, might represent the missing link between oncogenic transformation and pro-inflammatory activation in ECD. Objectives: In this study, we aimed at determining the role of TI in the pathogenesis of ECD, and to evaluate the therapeutic potential of targeting this mechanism for the treatment of inflammation. Methods: We developed innovative models to study ECD pathogenesis in vitro (based on lentiviral transduction and ectopic expression of BRAFV600E in primary human monocytes), as well as ex vivo (3D culture of ECD tissue biopsies in bioreactor). Functional and mechanistic features of TI, including typical changes in cell energy metabolism and epigenetics, were investigated by assessing I) cytokine and lactate production; II) mitochondrial respiration with Seahorse flux analyzer; III) glucose, glutamine and cholesterol metabolism with unbiased and targeted metabolomics analyses; IV) epigenetic changes with ChIP PCR; V) transcriptome changes with RNA sequencing. Results: Activation of the MAPK pathway induced by BRAFV600E in macrophages induces changes in the epigenetic and gene expression landscape, cell energy metabolism, and cytokine production characteristic of TI. In particular, changes in cell energy metabolism of macrophages are characterized by increased glycolysis, glutamine metabolism, and cholesterol synthesis. This metabolic rewiring is needed to sustain rampant, constitutive production of pro-inflammatory cytokines. Conclusion: A role emerges for TI in the pathogenesis and pro-inflammatory activation of ECD. However, maladaptive activation of this mechanism is likely common to the pathogenesis of other inflammatory and rheumatologic diseases. Since drugs targeting TI programs are already entering the clinical arena, the identification of this mechanism in the pathogenesis of inflammatory and rheumatologic conditions may promptly translate into novel, effective treatment options for affected patients. Disclosure of Interests: Riccardo Biavasco Employee of: Bluebird, Raffaella Molteni: None declared, Davide Stefanoni: None declared, Marina Ferrarini: None declared, Elisabetta Ferrero: None declared, Simone Cenci: None declared, Simone Cardaci: None declared, Alessandra Boletta: None declared, Laura Cassina: None declared, Gianfranco Di Stefano: None declared, Jorge Dominguez Andres: None declared, Claudio Doglioni: None declared, Travis Nemkov: None declared, Ivan Merelli: None declared, Angelo D'Alessandro: None declared, Eugenio Montini: None declared, Mihai Netea: None declared, Lorenzo Dagna: None declared, Giulio Cavalli Consultant of: SOBI, Pfizer, Sanofi, Novartis, Paid instructor for: SOBI, Novartis, Speakers bureau: SOBI, Novartis